SEGMENTASI DAN PEMISAHAN SEL DARAH PUTIH BERSENTUHAN MENGGUNAKAN K-MEANS DAN HIERARCHICAL CLUSTERING ANALYSIS PADA CITRA LEUKEMIA MYELOID AKUT - Aryo Harto; Chastine Fatichah (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2017)
The success of identification and classification on diagnosing acute myeloid leukemia (AML) diseases based on image processing relies heavily on segmentation result. Segmentation on peripheral blood smear images aims to separate the leukocytes region with others region. To increase the segmentation accuracy on AML images, a few things regarding lighting condition, contrast, staining variations and the existence of touching cells must be overcome. In this study a method for leukocytes segmentation and separate the touching cell on AML images using cluster analysis with K-Means and hierarchical clustering analysis (HCA) is proposed. K-Means method is used to analyze the cluster for AML images segmentation. The AML image datasets with various staining variations is segmented using K-Means method. The existence of touching cells is separated using HCA method which produce a stable clusters result. Segmentation and cell separation will be processed on local region or sub-image which is obtained from AML images cropping. From the evaluation results in 40 images of AML dataset, the proposed method is capable to properly segment the white blood cells region and separating the touching cell into a single cells. The average value of the segmentation results is 0.977 for precision, 0.885 for recall and 0.928 for Zijdenbos similarity index (ZSI) in white blood cell region. While in nucleus region the average value is 0.975 for precision, 0.924 for recall and 0.948 for ZSI. On cell counting, the error rate is also low which about 7.68%.